Evaluación de una experiencia de aula con un diseño basado en la teoría de la elaboración - Macías, Ascensión; Maturano, Carla Inés; Castro, José I. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1997)
This work proposes a model of a curricular design in Physics and its application in the classroom. It is developed according to the guidelines of the elaboration theory and it is put into practice in a basic university course. It includes an analysis of the structure of knowledge and an organization of the contents involved at different levels. Besides, it provides information about what and how to teach and what and how to evaluate. The results achieved in the classroom according to what is prescribed in this design about Waves and Sound are analyzed and discussed in this paper.